2022
DOI: 10.1590/1984-3143-ar2022-0063
|View full text |Cite
|
Sign up to set email alerts
|

Secretion pattern of canine amniotic stem cells derived extracellular vesicles

Abstract: Extracellular vesicles (EVs) derived from stem cells (SCs) have regenerative potential and the possibility of being used in treating chronic diseases. EVs present lower risk of tumorigenicity and easily to isolation and storage. Therefore, this research aims to compare the morphological characteristics of the EVs (up to 150nm) derived from stem cells obtained from canine amniotic membranes in different passages during the in vitro culture. For this, cells from the amniotic membranes were isolated, cultured, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Considering that cBM-MSCs and cAD-MSCs are almost equivalent in their ability to inhibit T cell activation, this observed difference does not appear to reflect a specific biological property [90,91]. Studies focused on increasing the number of exosomes collected have shown that EVs are more abundant in P0 of cultured amniotic MSCs compared with later passages, suggesting that this passage is most suitable for application in preclinical testing [92]. Notably, the same exosomes isolated from amniotic MSCs, if used as a supplement to MSC cultures, could increase the cell expansion rate because P1 cells have more metabolic activity compared to P2 cells [93].…”
Section: Characterization Of Canine Msc-derived Evs and Possible Fact...mentioning
confidence: 91%
“…Considering that cBM-MSCs and cAD-MSCs are almost equivalent in their ability to inhibit T cell activation, this observed difference does not appear to reflect a specific biological property [90,91]. Studies focused on increasing the number of exosomes collected have shown that EVs are more abundant in P0 of cultured amniotic MSCs compared with later passages, suggesting that this passage is most suitable for application in preclinical testing [92]. Notably, the same exosomes isolated from amniotic MSCs, if used as a supplement to MSC cultures, could increase the cell expansion rate because P1 cells have more metabolic activity compared to P2 cells [93].…”
Section: Characterization Of Canine Msc-derived Evs and Possible Fact...mentioning
confidence: 91%